RETRACTED: A method of developing road surfaces increase the level of environmental safety through the use of recycled tire waste - Omonov Makhmud; Djiyanboyev Sirojiddin (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001